High-density EEG sleep correlates of cognitive and affective impairment at 12-month follow-up after COVID-19. (August 2022) - Rubega, Maria; Ciringione, Luciana; Bertuccelli, Margherita; Paramento, Matilde; Sparacino, Giovanni; Vianello, Andrea; Masiero, Stefano; Vallesi, Antonino; Formaggio, Emanuela; Del Felice, Alessandra
Highlights: Sleep spindles may be a biomarker of psycho-affective symptoms in long COVID-19. Survivors perceive a decreased quality of life and post-traumatic stress symptoms . Post-traumatic stress symptoms may crucially contribute to cognitive impairment. Abstract: Objective: To disentangle the pathophysiology of cognitive/affective impairment in Coronavirus Disease-2019 (COVID-19), we studied long-term cognitive and affective sequelae and sleep high-density electroencephalography (EEG) at 12-month follow-up in people with a previous hospital admission for acute COVID-19. Methods: People discharged from an intensive care unit (ICU) and a sub-intensive ward (nonICU) between March and May 2020 were contacted between March and June 2021. Participants underwent cognitive, psychological, and sleep assessment. High-density EEG recording was acquired during a nap. Slow and fast spindles density/amplitude/frequency and source reconstruction in brain gray matter were extracted. The relationship between psychological and cognitive findings was explored with Pearson correlation. Results: We enrolled 33 participants ( 17 nonICU) and 12 controls. We observed a lower Physical Quality of Life index, higher post-traumatic stress disorder (PTSD) score, and a worse executive function performance in nonICU participants. Higher PTSD and Beck Depression Inventory scores correlated with lower executive performance. The same group showed a reorganization of spindle cortical generators. Conclusions: Our results show executive and psycho-affective deficits and spindle alterations in COVID-19 survivors – especially in nonICU participants – after 12 months from discharge. Significance: These findings may be suggestive of a crucial contribution of stress experienced during hospital admission on long-term cognitive functioning.